If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = (3h + -1) Reorder the terms: 15 = (-1 + 3h) Remove parenthesis around (-1 + 3h) 15 = -1 + 3h Solving 15 = -1 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. 15 + -3h = -1 + 3h + -3h Combine like terms: 3h + -3h = 0 15 + -3h = -1 + 0 15 + -3h = -1 Add '-15' to each side of the equation. 15 + -15 + -3h = -1 + -15 Combine like terms: 15 + -15 = 0 0 + -3h = -1 + -15 -3h = -1 + -15 Combine like terms: -1 + -15 = -16 -3h = -16 Divide each side by '-3'. h = 5.333333333 Simplifying h = 5.333333333
| 2-7[9-(6y-6)]= | | -4.65+0.19x=23.85 | | 7.4p-9.2p=-2.6+5.3 | | 5x^2-9x-80=0 | | -4+5x=-4x-4 | | Y-12=24 | | 7=4(5-2x)+3y | | 3(h-4)=-.5(24-6h) | | 7(3x-2)+18x+7=12x+7 | | (4n+17)+(n-2)=180 | | 9+t=14 | | (x+4)(x+4)+6=87 | | x+2=2x+15 | | 20+(-26)+34-(-37)-62= | | 10x^2+15x-8x-12=0 | | 3(x-3)+4(x)=9 | | 3*b-4=5v-2 | | (12x^2)-4x-5=0 | | 2(w-8)=4 | | 11.2j+11.55=j+10.1j+10.35 | | 13x+13=5x+11 | | x(x-20)=-20(2x+5) | | (2a+5)(a-6)= | | (15x^2+70x+25)=0 | | 2*s+3*s-1=18 | | 2(x+5)=3(x-(2-x)) | | 6*h+4=-2h | | 3(6+5x)=2(-5+4x) | | x^2-8x-84=0 | | -3=3(c+9) | | y=-3X^2-12X-11 | | (x^2)-12x+35=0 |